New root endophytic water borne conidial fungi from Kumaun Himalaya - Sati, S. C.; Pathak, Richa (Current Botany, 2017)
Water borne conidial fungi occurring in living roots of healthy plant growing in the wet and ravine areas of Dogaon and Ramgarh, Nainital, Kumaun Himalaya (India) were isolated as root endophytes. A total of 15 species (Alatospora acuminata, Anguillospora longissima, Beltrania rhombica, Campylospora chaetocladia, Claviriopsis aquatica, Cylindrocarpon aquaticum, Flagellospora penicilloides, Helicomyces roseus, Helicosporium lumbricoides, Pleurophragmium sonum, Pestalotiopsis submersus, Seridium sp, Setosynnema isthomosporum, Tetrachaetum elegans and Tetracladium marchalianum) of endophytic aquatic fungus were recovered as root endophytes of various host plants. Three species viz. Helicosporium lumbricoides, Pleurophragmium sonum and Setosynnema isthomosporum isolated from the roots of pteridophytes and grasses were found as new root endophytes. Among the studied host plants five plant species were also found as new hosts.